Factors Affecting the Mental Health of Chronic Disease Patients in Hospitals - M Ramadhani Firmansyah; Agus Dwi Pranata; Nora Harminarti; Sahariah (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Chronic disease is a long-term condition that affects not only the physical health, but also the mental health of the patient. Chronic disease patients often experience stress, anxiety, and depression due to prolonged treatment, limited activity, and varied social support. Mental health problems that are not treated properly can reduce the quality of life and patient adherence to treatment. This study aims to analyze the factors that affect the mental health of patients with chronic diseases in RSUD dr. Rasidin Padang. The research method used is quantitative research with cross-sectional design. A sample of 50 chronic disease patients undergoing treatment at RSUD dr. Rasidin Padang, selected using purposive sampling technique. Data analysis was conducted univariate and bivariate using Chi-Square test, and multivariate analysis using logistic regression. The results showed that as many as 56% of respondents experienced moderate to severe mental health disorders. The Chi-Square test showed a significant association between social support with mental health (p = 0.002), long of illness with mental health (p = 0.015), and treatment adherence with mental health (p = 0.008). The results of logistic regression showed that social support was the most dominant factor affecting the mental health of chronic disease patients (OR = 4.25; CI 95%: 1.62–11.18). The conclusion of the study was that social support, length of illness, and treatment adherence had a significant effect on the mental health of chronic disease patients. The implications of this study are expected to be the basis for health workers to improve holistic approaches through mental health screening as well as strengthening psychosocial support in the service of chronic disease patients in hospitals.